Legal Protection for Victims of Minor Crimes against Assets by Child Perpetrators in a Restorative Justice Perspective - Maharani, Febrianika (Universitas Islam Lamongan, 2023)
AbstractIndonesia, as a country that upholds legal norms and human rights (HAM), has a major role in ensuring that every citizen gets protection for their rights, including the rights of victims of criminal acts. The position of victims in the criminal justice system as parties seeking justice has so far received little attention, this is a form of injustice for victims. In the event that a criminal act is committed by a child, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System provides provisions for using a restorative justice approach through diversion in its resolution, the involvement of the perpetrator and victim in the diversion process aims to produce a win-win solution in order to achieve justice for all parties. Based on this, the author feels it is necessary to study this legal issue more deeply to find a solution to the problem in order to create a sense of justice for all parties. Based on this, the author feels it is necessary to study this legal issue more deeply to find a solution to the problem in order to create a sense of justice for all parties.Â Â